2003
DOI: 10.4269/ajtmh.2003.68.647
|View full text |Cite
|
Sign up to set email alerts
|

Placental and Oral Delivery of Schistosoma Mansoni Antigen From Infected Mothers to Their Newborns and Children

Abstract: Abstract. A 63-kD Schistosoma mansoni antigen was detected in 149 (86%) of 174 umbilical cord blood sera from infected women at delivery. Specific IgG antibodies to this antigen were also detected in 80% of cord blood sera. The 63-kD antigen showed the same molecular mass by Western blotting when isolated from cord blood, maternal blood, breast milk, and urine from women infected with S. mansoni. This antigen was detected in the urine of 25 infants born to infected mothers and followed for 18-24 months after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…The transplacental transport of soluble egg and adult worm antigens and their detection in the newborn have been documented in multiple reports (4,9,24,31,46,49). For example, Hassan et al detected an S. mansoni carbohydrate antigen in 66% of the urine samples from newborns of S. mansoni-infected mothers (n ϭ 45) (24).…”
Section: Discussionmentioning
confidence: 99%
“…The transplacental transport of soluble egg and adult worm antigens and their detection in the newborn have been documented in multiple reports (4,9,24,31,46,49). For example, Hassan et al detected an S. mansoni carbohydrate antigen in 66% of the urine samples from newborns of S. mansoni-infected mothers (n ϭ 45) (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have developed FgCA-27 ELISA, which successfully detected the 27-kDa Fasciola antigen with a detection limit of 8 ng/ml in human serum samples. The presence of Fasciola antigens in free form in the circulation of infected individuals may be attributed to continuous shedding and release of circulating antigens as a possible escape mechanism by the parasites, to reinfections, and to exposure to maternal antigens that may lead to developing tolerance rather than immunity to free antigens of natural infections (50). Moreover, the presence of high titers of specific IgG antibodies in the sera of infected individuals does not indicate a complete elimination of the pathogen; such high titers of antibodies may not neutralize all of the circulating antigens, i.e., via immune complex formation, and also, the specific IgM antibody response will not be stimulated for new infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although isolated reported studies have demonstrated direct trafficking of schistosome worms and whole eggs to the placental compartment in humans, this event appears to be relatively rare and is difficult to assess (40). Exposure and transfer of soluble worm and egg antigens across the placenta, however, is well documented and occurs in the majority of human pregnancies complicated with schistosome infection (41). We therefore utilized schistosome SEA in our experiments as a starting point for examination of the effect that schistosome infection might have on trophoblast cells.…”
Section: Figmentioning
confidence: 99%